The Morocco Policy Analysis Model : Theoretical Framework and Policy Scenarios - Achour, Aya.; Bulir, Ales.; Chafik, Omar.; Remo, Adam. (Washington, D.C. : International Monetary Fund, 2021)
The Morocco Policy Analysis model (MOPAM) was created in the Bank Al-Maghrib to simulate the impact of external developments, domestic macroeconomic policies, and structural reforms on key macroeconomic aggregates. We describe its structure and demonstrate its operation on two medium-term scenarios: (1) fiscal consolidation to stabilize the debt-to-GDP ratio and (2) the effects of the COVID-19 shock, including the endogenous fiscal and monetary policy response.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Debt Management; Debt; Foreign Exchange; Informal Economy; Underground Econom